The repercussions of the Coronavirus (COVID-19) pandemic on achieving the goals of the social dimension of sustainable development (2030) in the Arab region - بن عمورة, سمية; هولي, رشيد (Finance and Business Economies Review, 2020)
Through this research, we aim to identify the repercussions that the Corona Covid-19 pandemic can have on the goals of the social dimension of sustainable development for the year 2030 in the Arab region, by using the descriptive and analytical methodology. We have concluded that this pandemic constitutes a major obstacle for all Arab countries to achieve these goals on time, and will lead to the loss of several gains that were made before the pandemic, due to the size of the damage left, and the depth of the crisis in which the world flops.